O verdadeiro obstáculo à saúde mental na República Dominicana - Lajara Báez, Bianca (Pensando Psicología, 2023)
The purpose of this reflection article is to raise awareness of the situation of mental health services in the Dominican Republic. Problem areas that may be preventing the implementation of proposals for psychological services and the growth of initiatives already put into action are identified. It is concluded that the neuralgic point of the obstruction of projects and opening of services continues to be the lack of direct expression of the population that needs it and the stigma towards those who do so.
Keywords: saúde mental; República Dominicana; saúde pública